2021
DOI: 10.3390/foods10112636
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Precision-Controlled Temperature and Relative Humidity on Artificial Ripening and Quality of Date Fruit

Abstract: Due to climatic variation, in-situ date palm fruit ripening is significantly delayed, and some fruits (Biser) cannot become ripe naturally on the tree. Because of that issue, the vast quantity of produce is mere wasted. Few traditional methods are adopted to ripe these unripe fruits through open sun drying or solar tunnel dehydration techniques. However, these methods have minimal use due to ambient temperature and relative humidity (RH) instability. Therefore, the present study was designed to find a precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Our study also showed that the moisture content and water activity of date palm fruits were increased by about 14.31% and 30.61%, respectively, after 6 months of storage. Mohammed et al [ 14 ] recorded a 19.05% moisture content and 0.76 water activity in date fruits (cv. Khalas) stored at 5 °C and 80% RH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also showed that the moisture content and water activity of date palm fruits were increased by about 14.31% and 30.61%, respectively, after 6 months of storage. Mohammed et al [ 14 ] recorded a 19.05% moisture content and 0.76 water activity in date fruits (cv. Khalas) stored at 5 °C and 80% RH.…”
Section: Resultsmentioning
confidence: 99%
“…The flavor, color, texture, and nutrients of fruits are preserved when correctly stored. The most critical factors that affect the longevity of fruits after harvesting and during storage are temperature and relative humidity [ 12 , 13 , 14 ]. Optimal relative humidity helps prevent weight loss, the spread of fungal diseases, and physiological disorders [ 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit sample weight was determined after 48 h to calculate the date fruit MC according to the Association of Official Analytical Chemists (AOAC) [ 34 ]. The total soluble solids (TSS) of the date fruits were measured using a digital laboratory refractometer (RFM 840, Richmond Scientific Ltd., Unit 9, Lancashire, UK) [ 33 ]. The fruit’s total sugar (TS) was measured using the anthrone–sulfuric acid colorimetry method.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh dates have a limited shelf life and are susceptible to spoilage, which can lead to economic losses for producers and suppliers. The problem of accurate shelf life estimation for fresh dates is essential for various stakeholders involved in the production, supply, and consumption of dates [ 32 , 33 ]. By addressing this problem, we can enhance food safety, reduce waste, and improve the overall efficiency and sustainability of the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of date palm cv. Khalas stored at 5 • C and 80% RH did not show insect activity or degradation in fruit quality and enhanced their shelf-life [47]. Soft and semi-soft date fruits can be preserved by storing them at 5 • C or lower, preventing the development of various pests [48].…”
Section: Impact Of Iot-bc On Stored Fruit Characteristicsmentioning
confidence: 99%